Damping systems that are effective over a wide range of displacement amplitudes using metallic yielding component and viscoelastic damper in series. (14th May 2014) - Yamamoto, Masashi; Sone, Takayuki
SUMMARY A damper system that absorbs energy over a wide range of displacement amplitudes during building vibration was proposed. This system uses a serial connection of a metallic yielding component and viscoelastic damper with a displacement limit mechanism. Three types of the system were developed and tested: a diagonal bracing type, inverted V bracing type, and wall type. The test results showed that all these systems have damping ratios higher than 8% at small vibration amplitudes on the order of 0.1 mm. For a large vibration, a displacement limit mechanism with two pins limited the displacement of the viscoelastic damper as designed. Analytical simulations established that the system reduced the acceleration and the story drift to 60–70% and 80%, respectively, during a small earthquake compared with a conventional metallic yielding damper system. Furthermore, it showed an equivalent control performance during a severe earthquake. The damper system requires that a clearance be maintained for the displacement limit mechanism. However, this may be lost through construction error, residual displacement after an earthquake, and temperature effects. The changes in the clearance due to these effects were discussed. Copyright © 2014 John Wiley & Sons, Ltd.